‘The Pots on Our Roads’The Diaspora Fleet and Harare’s Urban Commuter System - Mazarire, Gerald C.; Swart, Sandra (Brill, 2016)
This article explores the role of the ‘diaspora fleet’ in Harare’s urban commuter system. Imported vehicles in the form of haulage trucks and commuter buses were one of the popular and visible forms of diasporic investment over Zimbabwe’s difficult decade spanning from 2000 to about 2010. The article argues that this diaspora fleet occupies a significant place in the history of commuting in Harare. Diasporic investment introduced a cocktail of European vehicles that quickly became ramshackle and ended up discarded in scrap heaps around the city. These imports and the businesses based on them destroyed the self-regulatory framework existing in the commuting business. This disruption was facilitated by the retreat or undermining of the state and city council regulatory instruments, which in turn created a role for middlemen, who manoeuvred to perpetuate a new and chaotic system known as ‘mshika-shika [faster-faster]’, based on a culture of irresponsible competitive gambling. This chaotic system remains in place today to the chagrin of city council planners and traffic police. Its origins, we argue, lie in the cultures and practices introduced by the diasporan vehicle fleet.